2020
DOI: 10.14202/vetworld.2020.801-806
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the nutritive value of corn stover and king grass in complete feed on Ongole steer calves productivity

Abstract: Aim: This study aimed to assess the nutritional values of corn stover and king grass (Pennisetum purpupoides) in complete feed on the productivity of male Ongole steer calves. Materials and Methods: This study was conducted in two steps: Cattle adaptation and data collection. Cattle adaptation was carried out for 2 weeks, and the cattle were fed the experimental feed. The experimental feed was formulated into five combinations: R1 (50% king grass); R2 (12.5% corn stover +7.5% king grass 50% concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Kanyinji et al (2017) reported negative effects of inclusion of CS in the ration of goats. In agreement with the current ndings, Tuturoong et al (2020) reported an increased DM, OM, CP and NDF digestibility in the small ruminants fed CS based ration. The decreased nutrient digestibility by dietary inclusion of WS as crop residue may possibly be due to higher lignin contents than corn stover.…”
Section: Discussionsupporting
confidence: 92%
“…Kanyinji et al (2017) reported negative effects of inclusion of CS in the ration of goats. In agreement with the current ndings, Tuturoong et al (2020) reported an increased DM, OM, CP and NDF digestibility in the small ruminants fed CS based ration. The decreased nutrient digestibility by dietary inclusion of WS as crop residue may possibly be due to higher lignin contents than corn stover.…”
Section: Discussionsupporting
confidence: 92%
“…670. It could result that the feeding has not, in general, met the recommended feed needs, either quality or quantity, to push the weight growth so the addition of feed costs is needed to shorten the rearing time and increase the body weight [21]. The feed quality improvement will be beneficial for reducing the fattening time and yielding higher daily weight growth [22] so that the farmer's income increases.…”
Section: Effect Of Feed Cost On Profitmentioning
confidence: 99%
“…One reason for livestock productivity being low is the scarcity of high-quality feed. Not only is feed limited by its nutritional value, but also by its sustainability [2], [3]. During the dry season, it will be more challenging to obtain feed because it will typically be abundant during the rainy season.…”
Section: Introductionmentioning
confidence: 99%